2018
DOI: 10.1007/s00436-018-5881-z
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal helminths of gray wolves (Canis lupus lupus) from Sweden

Abstract: As the Scandinavian wolf population is limited in size, it is only rarely subject to systematic studies on its disease biology, especially gastrointestinal parasites. Therefore, this study aims to describe the prevalence of gastrointestinal helminths of gray wolves hunted on a limited license as a part of a wildlife management program. Helminths of 20 wolves were examined post mortem by macroscopy and coprology. Intestinal worms of five species were recovered from 18 wolves (90%): Uncinaria stenocephala (90%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…To our knowledge, this is the first broad investigation of helminth and protozoan parasites in grey wolves of three different geographical regions. The data complement and broadens several other geographically more restricted studies using necropsy or coprology (Guberti et al, 1993; Stronen et al, 2011; Bryan et al, 2012; Schurer et al, 2016; Lesniak et al, 2017a, 2017 b; Al-Sabi et al, 2018). Our findings correlate well with the ancestry and the ecology of the three wolf populations.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…To our knowledge, this is the first broad investigation of helminth and protozoan parasites in grey wolves of three different geographical regions. The data complement and broadens several other geographically more restricted studies using necropsy or coprology (Guberti et al, 1993; Stronen et al, 2011; Bryan et al, 2012; Schurer et al, 2016; Lesniak et al, 2017a, 2017 b; Al-Sabi et al, 2018). Our findings correlate well with the ancestry and the ecology of the three wolf populations.…”
Section: Discussionsupporting
confidence: 82%
“…The impact of free-ranging dogs is illustrated by the surprisingly high proportion of samples with C. boehmi (80.7%), exclusively detected in PNALM. Only recently, Al-Sabi et al (2018) reported a high proportion of 60% of C. boehmi in wolves of Sweden. The high percentage of this mainly directly transmitted parasite suggests a very efficient transmission and an important contamination of the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our low parasite prevalence and richness can be associated with seasonal variation effects in the Extremadura region, such as moisture and, especially, temperature, which has shown a trend towards higher maximum extreme values [38], affecting the abundance and activity of intermediate host and parasite development [39], but also the conservation of the samples collected directly from the ground. Events of parasitic fauna extinction, due to the absence of the required intermediate host [40] or the non-predation of key intermediate species [41], but also host body mass and life-history traits, can be considered other associated factors [42].…”
Section: Discussionmentioning
confidence: 99%
“…Toxocara canis also infects wolves with different prevalence in Italy (17%, Guberti et al, 1993; 33%, Fiocchi et al, 2016), Germany (5%, Bindke et al, 2017; 11%, Lesniak et al, 2017), Belarus (21%, Shimalov and Shimalov, 2000), Estonia (8%, Moks et al, 2006), Poland (6.9%, Borecka et al, 2013) and Spain (6%, Segovia et al, 2003). No wolves infected with T. canis were diagnosed in Sweden (Al-Sabi et al, 2018). In Australien wild dogs (dingoes) the prevalence of T. canis was up to 46% from Wet Tropics region around Cairns, Far North Queensland (Smout et al, 2013), and 27.8% of 18 dingoes from Fraser Island (Queensland) with close ntcoact with human habitation were infected (Mackenstedt et al, 2015).…”
Section: Soil-transmitted Nematode Zoonosesmentioning
confidence: 99%